Profil Kemampuan Argumentasi Mahasiswa Pendidikan Kimia Semester I : Learning Gap yang Terbentuk Selama Pembelajaran di Masa Pandemi - Fatchiyatun Ni'mah; Mawadatur Rohmah (Jurnal Ilmiah Kanderang Tingang, 2023)
Technological developments that move quickly can be balanced with learning that can accommodate the development of students as a whole. One of the skills needed is argumentation ability. Argumentation skills can train students to develop critical thinking skills and become good policy makers. However, with the pandemic and learning being carried out online, it has caused learning gaps, one of which is in terms of argumentation skills. The research method used is a case study with the aim of describing the profile of the first semester students' argumentation abilities through practicum reports. Analysis of the quality of student arguments using the adjusted Toulmin model. Based on the results of data analysis, it was found that 64.44% of student arguments at level 1E and 32.22% of student arguments at level 2.